Internet censorship law: a Comparative study between Malaysia and Singapore / Fairuz Naziha Mohamad, Azarith Sofia Aziz and Nor Nazifah Ahmad Nordin. - Mohamad, Fairuz Naziha; Aziz, Azarith Sofia; Ahmad Nordin, Nor Nazifah (2013)
There is a growing concern that Internet access is being restricted by governments through various legislation. Government engaged in Internet censorship, among others to protect public morality, suppress subversive material or eliminate threats to national security. Different countries have a different law and policies with regards to Internet governance. This research attempts to conduct a comparative study of Internet censorship law between Malaysia and Singapore. This paper examines the legal framework of Internet censorship currently applied in Malaysia. The government of Malaysia has repeatedly emphasized that Internet would not be subjected to censorship and this is provided for under the Communication and Multimedia Act 1998. However, this stance has since changed with the amendment to Evidence Act 1949. Internet is being regulated in Malaysia by using the conventional media censorship laws such as the Defamation Act, Film Censorship Act and Sedition Act. The research studies the application of Internet censorship in Malaysia. Internet is being censored by government mainly to preserve harmony in the multiracial society and to protect national security. However, there is lack of clear direction in the Malaysian law regarding Internet censorship which leads to confusions among the public. For the purpose of comparison this research is looking into the Internet censorship legal framework of Singapore. In Singapore, like other media, Internet is under the jurisdiction of Media Development Authority (MDA). Singapore also applies the Sedition Act in implementing Internet censorship. Almost similar to Malaysia, Singapore aims in regulating Internet is to protect and safeguard public interests. However, the application of Internet censorship is quite different from Malaysia as in Singapore, there was no pledge that Internet will not be censored.